A importância do tratamento de água no controle de parasitoses intestinais: abordagem com escolares - Isângela Rodrigues Bastos (2020)
Enteroparasitosis are considered the most common diseases in the world, being more prevalent in school-age children. The concern with water quality is imminent, as water pollution causes several of these diseases. The school has a primary role in preventive health educational strategies and the investigative approach can contribute to this learning because contextualized problematization situations can promote discoveries and construction of significant and relevant scientific knowledge for students. Thus, this work aimed to elaborate a Investigative Teaching Sequence and build with the students of the 2nd year of high school of a school of Presidente Bernardes/MG the knowledge about enteroparasitosis of the municipality and the importance of water treatment in this control. This project was a partnership with the Municipal Health Department that made the parasitologic survey in schools, through stool examinations. The students, in addition to following this work, participated in a lecture on water treatment, conducted bibliographic surveys on water collection and treatment in the municipality and conducted a study directed from the parasitosis found: schistosomes, ascaridiasis, enterobiasis and teniasis. These activities allowed the students to solve the proposed problematization and prepare an informative booklet. The partnership signed, together with the research processes, provided students to act with autonomy, achieving the objectives and approaching scientific literacy. For this scope, the teacher’s mediation proved to be important throughout the process. And the students, seeing themselves as protagonists of their productions, felt confident in accepting new school challenges.